1995
DOI: 10.1152/ajpregu.1995.268.1.r78
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and the acute phase response to influenza virus in mice

Abstract: This study characterized selected aspects of the acute phase response after intranasal inoculation of mice with two doses of mouse-adapted influenza virus differing in lethality. Mice given 140 plaque-forming units (PFU) of virus (58% survival) gradually decreased food and water intake to nearly zero over 6 days; survivors then slowly increased intakes. Declines in these behaviors were parallel to decreases in body temperature and general locomotor activity and were associated with elevated activities of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 0 publications
8
87
1
2
Order By: Relevance
“…In the present study, we define central but opposite effects of COX-1 and COX-2 enzymes in the host response to this infection. Hypothermia and weight loss are well documented features of viral influenza infection in the mouse (25)(26)(27)(28)(29)(30). In the present study, we observed some differences in the early temperature response to influenza infection in the COX-1 Ϫ/Ϫ and COX-2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, we define central but opposite effects of COX-1 and COX-2 enzymes in the host response to this infection. Hypothermia and weight loss are well documented features of viral influenza infection in the mouse (25)(26)(27)(28)(29)(30). In the present study, we observed some differences in the early temperature response to influenza infection in the COX-1 Ϫ/Ϫ and COX-2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 55%
“…Acute-phase response is defined as the dose-dependent behavioral and physiological response of host organisms to infections and is regarded as a nonspecific host defense response. 75 The acute-phase response includes fevers of different magnitudes, changes in food and water intake in mice as well as decreases in activity and body temperature, which again have been correlated to cytokine activity after influenza virus infection. 75 On recognition of viral components, PRRs initiate production of a variety of cytokines, mainly type-1 INFs (IFN-b and -a), and induce innate and adaptive immune responses.…”
Section: Cytokines As the Initial Line Of Defensementioning
confidence: 99%
“…Interleukin 6 exhibits multifunctional activities that are largely proinflammatory and their release has been correlated with the same clinical symptoms and signs related to influenza in mice. 75 Interferon g inducible protein is a chemokine that is being studied for its role in the severity of lung damage after IAV infection. BALB/c mice infected with H5N1 after administration of IP-10 presented with more fulminant and necrotizing diffuse alveolar and bronchiolar damage with lymphocyte infiltration compared to infected mice without IP-10 administration.…”
Section: Role Of Cytokines/chemokines and Their Receptorsmentioning
confidence: 99%
“…During pulmonary infections cytokine production is mainly restricted to the lung and it seems that diffusion of cytokines across the bloodalveolar barrier is rather limited [87]. Consequently, the highest amounts of cytokines are detected at the lung level, and plasma cytokine levels are generally low or undetectable [11,33]. This situation contrasts with that seen during septicaemia, where endothelial and blood cells are the primary cytokine producers and systemic effects, such as shock and multiple organ failure, predominate.…”
Section: Cytokine Effects On the Respiratory Tractmentioning
confidence: 99%